Key word, information, memory clue (kim) as a cooperative learning strategy to develop efl basic writing skills amongst ninthgrade students at unidad educativa “Marieta de Veintimilla” academic period 2014-2015 - Aguirre Feijoó, Tatiana Fernanda (2016)
The present research work focused on the use of Key Word, Information, Memory Clue as a cooperative learning strategy to develop writing skills amongst ninth- grade students. An intervention plan consisting of twenty-two lesson plans was carried out to improve the skill. Tests and questionnaires were used to measure students’ weaknesses and progress on writing as well as their behavior and attitudes toward the strategy before mentioned. The scientific, descriptive, analytic-synthetic and statistic method were used to describe and analyze the results and finally, draw conclusions. The results of the posttest and post questionnaires displayed a big progress on students when writing. Based on these outcomes, it is drawn that the intervention was important because students´ scores improved